Review of the second edition of the book Qué es la Geografía, 2018 - Morales, Huáscar (2019)
Ruy Moreira belongs to the generation of geographers who renew the field of study from a critical view of capitalism. Movement marked by Milton Santos (1926-2001), the renovation of critical geography in Brazil has as protagonists the professor of the Universidad Federal Fluminense and other renowned authors such as Carlos Walter Porto Conçalves and Rogério Haesbaert. Moreira's work during the 70s, 80s and 90s focuses on the Man-Nature-Economy relationship from a Marxist perspective, in the following decades, to continue reflections on a general geographical theory and on the Brazilian socio-spatial configuration.